Non-Mendelian segregation influences the infection biology and genetic structure of the African tree pathogen Ceratocystis albifundus. Issue 4 (April 2018) - Lee, Dong-Hyeon; Roux, Jolanda; Wingfield, Brenda D.; Wingfield, Michael J.
Abstract: The African fungal tree pathogen, Ceratocystis albifundus, undergoes uni-directional mating type switching, giving rise to either self-fertile or self-sterile progeny. Self-sterile isolates lack the MAT1-2-1 gene and have reduced fitness such as slower growth and reduced pathogenicity, relative to self-fertile isolates. While it has been hypothesized that there is a 1:1 ratio of self-fertile to self-sterile ascospore progeny in relatives of C. albifundus, some studies have reported a significant bias in this ratio. This could be due to the fact that either fewer self-sterile ascospores are produced or that self-sterile ascospores have low viability. We quantified the percentage of self-sterile and self-fertile ascospores from ascospore masses in C. albifundus using real-time PCR. Primers were designed to distinguish between spores that contained the MAT1-2-1 gene and those where this gene had been deleted. A significant bias towards the self-fertile mating type was observed in all single ascospore masses taken from sexual structures produced in haploid-selfed cultures. The same result was observed from a disease outbreak situation in an intensively managed field of cultivated native trees, and this was coupled with very low population diversity in the pathogen. This was in contrast to the results obtained from ascospore masses taken from the crosses performed under laboratory conditions or ascomata on native trees in a non-disease situation, where either self-fertile or self-sterile ascospores were dominant. The results suggest that reproductive strategies play a significant role in the infection biology and genetic structure of C. albifundus populations.